501 word analogy questions (New York, 2002)
This book is designed to help you prepare for the verbal and reasoning sections of many assessment and entrance exams. By completing the exercises in this book, you will develop the skills necessary to tackle each type of analogy question
Keywords: Vocabulary tests,Kiểm tra từ vựng